The Implementation of Indeks Desa Zakat (IDZ) for Priority Areas of the Zakat Community Development (ZCD) Program for the Empowerment of Productive Mustahiq in South Kalimantan - Sri Maulida; Rizali .; Akhsanul Rahmatullah (International Journal of Zakat, 2018)
A number of different parties, from both the governmental and private sectors, have attempted various means of overcoming poverty, such as through a zakat institution. As an official zakat institution, BAZNAS has established the Zakat Community Development (ZCD) program. The ZCD program seeks to empower communities by targeting the mustahiq living in underdeveloped villages in terms of prosperity, facilities, and infrastructure. The program has the objective of enabling the members of mustahiq communities to help each other manage the funds provided by BAZNAS, so that their prosperity can be increased. Related to this program, BAZNAS has developed a measurement tool called the Indeks Desa Zakat, or IDZ, which emphasizes Islamic elements, such as those relating to religion, as its very important aspects, in addition to the economic, social, health, and education aspects. This research aims to answer questions regarding the overall condition of villages targeted for the ZCD program by central BAZNAS, in addition to identifying underdeveloped villages to prioritize for assistance. The results demonstrate that from the implementation of Indeks Desa Zakat (IDZ) calculations in the priority areas of ​​the ZCD program, it can be concluded that among the three research locations, RT 34 Beruntung Jaya Village is the village that should be most highly prioritized for a ZCD program, with an index value of 0.48. This value places the village in the good category based on the IDZ score range; therefore, it can be considered for assistance.